IT Adoption in Westports Customer Service and Alignment to Its Business Strategy - Vyithelingam, Jananandh (2008)
This dissertation looks at Information Technology (IT) adoption in Westports Malaysia’s customer service and its alignment to its business strategies. Westports has been leveraging on technology as its competitive advantage in addressing the growth and challenges of the ports and maritime industry. The literature presents the use of the Strategic Alignment Model (SAM) and a set of frameworks to model and assess IT-Business alignment in Westports. The assessment methods reveal outcomes that are linked to the factors (enablers) influencing IT-Business alignment in Westports. A survey was conducted among three departments, IT, Customer Service and Finance to determine the extent of the presence of the factors influencing IT-Business alignment and its effectiveness in Westports. The combination of the assessment methods and survey reveal that Westports’ IT is aligned to the business strategies due to support from top management, IT leadership, connections between IT and business planning and well prioritized IT projects. The survey has also uncovered potential issues that may impact on IT-Business alignment in the long-term if not addressed immediately.